Mineral nutrient status and heavy metal contents of an endangered endemic plant from İstanbul; centaurea hermannii - YILMAZ, AHMET; ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
AbstractCentaurea hermannii F. Hermann (syn: C. sisymbriifolia Arènes) is an endemic plant described from İstanbul,Turkiye. It is listed in the Red Databook of Turkish Plants as an endangered species (Ekim et al., 2000). It is aperennial plant with an erect, usually simple stem of 30-60 cm with decayed remains of petioles at the base. Leavesare sparsely pilose, lyrate, basal and lower leaves are petiolate. Flowers are orange, marginal and not radiant.Achenes are 3-6 mm long, 0,5- 2,8 mm wide; pappus 5,5 – 10,5 mm long. Flowers are present usually from lateMay through June and early July. Resides under Quercus or Pinus forest cover usually away from direct sunlightat an elevation of between 100-500m.Based on the idea that C. hermannii being an endemic plant may suggest that the regions where it grows may alsohave a special soil mineral element composition, special micro and macro climates and ecological conditions, soilsamples taken from the regions where this plant grows were examined in terms of heavy metal and mineralelements, and the results were compared with the heavy metal and mineral element levels found in different partsof the plant such as stem, root and leaves. Analyzes of Al, B, Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Na, Ni, Pb andZn elements were performed with the ICP-OES device. A soil and six plant samples were taken from the twodifferent populations of C. hermannii. The samples were then dried and measured and average values wereobtained for further evaluation.The characteristics of two locations that the samples were taken from are distinctive and deemed effective in heavymetal and mineral nutrient contents of the samples. First location, Arnavutköy is very close to busy road trafficand prone to heavy metal exposure in comparison to Aydos location which is far from roads, with slightly higherelevation and less human exposure. In this regard, the results obtained are as expected, since the levels of all 15elements in soil samples were higher in Arnavutköy samples. Differences of element levels varied between as lowas 5% in Fe and K, and as high as 20% in Cr, Co and Cu, and 23% in Ni contents. This difference can also beobserved in plants parts when the two locations are compared; with the stem and root samples from Arnavutköylocation containing higher amounts of all elements tested, whereas 13 elements were measured higher in leafsamples from Arnavutköy with the exception of Cr and Fe.When the heavy metal and mineral element levels were separately evaluated, Ca, Cd, Fe, K, MN, Na, Ni levelswere within normal limits in all plant parts from both locations. Al and B levels were 30-50% higher in rootsamples of both locations and within normal range in leaf and stem samples. Cr and Cu levels were above normallevels in all samples from both locations. Zn, Pb, Co and Mg levels were elevated in leaf and root samples fromboth locations. To summarize briefly, none of the elements were above toxic threshold with the exception of Cufor all samples and ZN for leaf and root samples from both locations.These results show that this endemic plant is not yet under heavy metal stress, but still exposed to heavy metalstress above normal levels. In the medium and long term, the possibility of changing the threat category should beevaluated as a result of the difficulties that this plant may experience in adapting to both habitat loss and increasedheavy metal exposure with growing urbanization and increased traffic congestion.Keywords: Heavy metal stress, Plant conservation, habitat loss, Extinction threat
Keywords: Yaşam Bilimleri; Bitki Biyolojisi; Çevre Biyolojisi; Temel Bilimler; Life Sciences; Plant Biology; Environmental Biology; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bitki ve Hayvan Bilimleri; Doğa Bilimleri Genel; Biyoloji ve Biyokimya; BİTKİ BİLİMLERİ; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; Agriculture & Environment Sciences (AGE); Natural Sciences (SCI); Life Sciences (LIFE); PLANT & ANIMAL SCIENCE; NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; PLANT SCIENCES; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Bitki Bilimi; Multidisipliner; Plant Science; Multidisciplinary